Cytoprotective effect of tangeretin in hydrogen peroxyde-inducedoxydative stress on human umbilical vein endothelial cells (HUVECs) - Riris Istighfari Jenie; Irfan Muris Setiawan; Ikhlas Muhammad Jenie; Haruma Anggraini Muflikhasari (Universitas Islam Indonesia, 2015)
Oxydative stress is known as a major trigger in cardiovascular dysfunction that leads to hypertension, atherosclerosis, and chronic heart failure. Polymethoxyflavone such as tangeretin and nobiletin has been reported to have biological activity including reducing cholesterol level and anti inflammation activity. The critical point that mediates atherosclerosis is the formation of stress oxidative which causes endothelial cells dysfunction.This study was conducted to explore the effect of tangeretin in protecting H2O2-induced oxidative stress on HUVEC. Cell viability was determined by using MTT assay. Cells were treated with different concentrations of tangeretin (12.5; 100; and 200 µM) for 24h before exposed to 600 µM H2O2 for 4h. Cells viability analyses showed that at low concentration (12.5 µM), tangeretin inhibited H2O2-induced cytotoxicity. Furthermore, it induced cells proliferation. However, at high concentration, it failed to protect HUVEC from H2O2-induced cytotoxicity and increased the cytotoxicity of H2O2. Based on this result, tangeretin in low concentration has a potential to reduce oxidative stress on HUVECs.